La implementación de ganadería regenerativa en el establecimiento "El Transporte" - Marinzalta, Mauro Andres; Marinzalta, Nicolás Ariel; Villalba, Santiago; Devesa, Antonia; Aramburú, Alina; Boggio, Federico (Universidad Nacional del Comahue, 2026)
Presentación oral y resumen